A Sustainable CIPP Evaluation-Based School Literacy Program: Program Literasi Sekolah Berbasis Evaluasi CIPP yang Berkelanjutan - Haryati, Resti; Fadliyah, Chairati; Rahmona, Fitria; Nabillah, Salsa; Friyatmi; Susanti, Dessi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Literacy is vital in shaping students' competencies in the information era. Specific Background: SMAN 5 Padang has implemented a literacy program aligned with the Merdeka Curriculum but faces challenges in integration and teacher involvement. Knowledge Gap: Few studies evaluate literacy programs comprehensively using the CIPP model at the high school level. Aims: This study evaluates the school’s literacy program using the CIPP model to analyze its relevance, resources, implementation, and outcomes. Results: The program improved reading interest by 26% and daily reading time by 20 minutes, with 78% of students actively using the literacy corner. However, teacher participation is low, reading materials are less varied, and program integration into learning remains limited. Novelty: The use of the CIPP model provides a structured evaluation rarely applied in literacy programs at this level. Implications: The findings offer strategic input for strengthening literacy programs through teacher engagement, material enrichment, innovation, and digital integration for sustainable impact.Highlight : The CIPP model helps evaluate the literacy program’s planning, implementation, and outcomes comprehensively. The program boosted reading interest but showed weak teacher involvement and limited reading material variety. Strengthening integration into classroom learning and fostering innovation are essential for sustainability. Keywords : School Literacy, CIPP Evaluation, Reading Culture, Teacher Roles, Literacy Innovation